Monthly Variation in the Macromolecular Composition of Phytoplankton Communities at Jang Bogo Station, Terra Nova Bay, Ross Sea - Kim, Kwanwoo; Park, Jisoo; Jo, Naeun; Park, Sanghoon; Yoo, Hyeju; Kim, Jaehong; Lee, Sang Heon (Frontiers in Microbiology, 2021)
Organic carbon fixed by photosynthesis of phytoplankton during the polar growing period could be important for their survival and consumers during the long polar night. Differences in biochemical traits of phytoplankton between ice-free and polar night periods were investigated in biweekly water samples obtained at the Korean “Jang Bogo Station” located in Terra Nova Bay, Antarctica. The average concentration of total Chl-a from phytoplankton dominated by micro-sized species from the entire sampling period was 0.32 μg L-1 (S.D. = ± 0.88 μg L-1), with the highest concentration of 4.29 μg L-1 in February and the lowest concentration of 0.01 μg L-1 during the ice-covered polar night (April to October) in 2015. The highest protein concentration coincided with the peak Chl-a concentration in February and decreased rapidly relative to the carbohydrate and lipid concentrations in the early part of polar night. Among the different biochemical components, carbohydrates were the predominant constituent, accounting for 69% (S.D. = ± 14%) of the total particulate organic matter (POM) during the entire study period. The carbohydrate contributions to the total POM markedly increased from 39 ± 8% during the ice-free period to 73 ± 9% during the polar night period. In comparison, while we found a significant negative correlation (r2 = 0.92, p < 0.01) between protein contributions and carbohydrate contributions, lipid contributions did not show any particular trend with relatively small temporal variations during the entire observation period. The substantial decrease in the average weight ratio of proteins to carbohydrates from the ice-free period (mean ± S.D. = 1.0 ± 0.3) to the ice-covered period (mean ± S.D. = 0.1 ± 0.1) indicates a preferential loss of nitrogen-based proteins compared to carbohydrates during the polar night period. Overall, the average food material (FM) concentration and calorific contents of FM in this study were within the range reported previously from the Southern Ocean. The results from this study may serve as important background data for long-term monitoring of the regional and interannual variations in the physiological state and biochemical compositions of phytoplankton resulting from future climate change in Antarctica.